Characterization of Household-Scale Pig Farming Wastewater and Evaluation of Treatment Efficiency Using Constructed Wetlands in Thanh Hoa Province, Vietnam - Nga, Bui Thi Van; Anh, Hoang Quoc; Tuan, Le Duc Anh; Rong, Chao (Sustainable Environmental Insight, 2026)
Pig farming wastewater from small-scale household systems in Vietnam presents significant environmental challenges due to its high concentrations of organic matter, suspended solids, and nutrients. This study aimed to (i) characterize wastewater generated from household pig farms in Thanh Hoa Province and (ii) evaluate the treatment performance of a hybrid constructed wetland (HCW) system as a post-treatment stage following biogas digestion. A survey was conducted at 20 representative households, each raising 10–50 pigs. A pilot-scale HCW system, consisting of a subsurface flow constructed wetland (SSF CW) followed by a free-floating plants constructed wetland (FFP CW), was operated continuously for 100 days at a flow rate of 150 l/day. Results indicated that the influent wastewater remained highly polluted after biogas treatment, with COD, TSS, TN, and TP concentrations exceeding regulatory limits. The HCW system achieved average removal efficiencies of 80.8% for COD, 84.0% for TSS, 79.6% for TN, and 75.4% for TP. The final effluent quality consistently met QCVN 62-MT:2025/BTNMT (Column B). These findings demonstrate that the HCW system is an effective, low-cost, and sustainable solution for improving wastewater treatment efficiency in small-scale pig farming systems, thereby contributing to environmental protection and sustainable rural development.